The influence of Co/Sr and Fe/Sr driers on film formation of high solid alkyd coatings - Pirš, Barbara (Acta chimica slovenica, 2015)
High solid (HS) alkyd resins with low amount of volatile organic compounds (VOC) were developed as the result of new VOC solvent directive that limit the amount of VOC in decorative paints. Due to specific chemical structure of HS alkyd resins and possible deterioration of some applicative properties the optimal combination of driers is an important subject of research. In our present work we studied the influence of Fe bispidon (Fe drier) and Co ethylhexanoate (Co drier) surface driers with Sr carboxylate (Sr drier) through drier on the film formation of HS alkyd coatings. The kinetics of autoxidation was analysed using FT-IR spectroscopy. Further, applicative properties like drying time and film hardness were examined. In the end, electrochemical impedance spectroscopy (EIS) was used to evaluate the quality of cured HS alkyd coating films after exposure in the humidity chamber. It was established that the addition of the Sr drier to surface driers accelerates the autoxidation process. As higher amounts of the Sr drier were added, final drying times were reduced and film hardness increased. The lowest diffusivity of ions through cured HS alkyd coating films was observed for Co/Sr and Fe/Sr drier combination at 1:1 concentration ratio.
Keywords: alkidna veziva; avtooksidacija; karakterizacija; premazi; trdota